The politics of the common law : perspectives, rights, processes, institutions - Gearey, Adam (Routledge-Cavendish, 2010)
Offers an introduction to the English legal system that places the common law in its contemporary context. This book examines the impact of the European Convention on the structures and ideologies of the common law, and suggests that there is a general jurisprudence of human rights stemming from the Human Rights Act.